Individual pension decision-making in a financialised landscape: a typology of everyday approaches. Issue 6 (2nd November 2021) - James, Hayley
ABSTRACT: In the UK, individuals are increasingly responsible for achieving an adequate retirement income, yet many people are not saving enough for later life. While we understand some of the structures that lead to differential pensions, we know very little about how people make decisions about their workplace pensions. This is a crucial question as an increasingly financialised landscape means that individuals must make financial decisions about whether to save, how much to save, whether and when to change investments. In this paper, I show that individual approaches to pension provision are not simply determined by structuring variables but are socially and culturally embedded, using qualitative interviews with purposively selected employees from three large private sector organisations. I propose a typology of four approaches to pension decision-making that connect to social and cultural meanings of everyday life, such as life status, identity and relationships. This typology challenges the economic models of rational decision-making that have been used to justify financialisation and highlights the need for later life provision which does not predominantly rely on individuals ability to save, taking into account social and cultural variations in financial behaviours as well as the inherent structural inequalities.